THE ROLE OF THE NOTARY REGIONAL SUPERVISORY BOARD IN RESPONDING TO VIOLATIONS OF NOTARY DUTIES AND POSITIONS - Rastra Ananda; Rohaini Rohaini; Siti Nurhasanah; Sunaryo Sunaryo (Faculty of Law, Universitas Lampung, 2022)
The Notary Supervisory Council (MPN) is here to improve services and legal protection for the public who use notary services. However, nowadays, there are more and more irregularities committed by notaries in carrying out their duties and positions, both administrative in nature and resulting in material losses to the public who use notary services. The imposition of sanctions is an effort by MPN, especially the Regional Supervisory Council (MPW) in order to provide sorrow for notaries who violate and appeal to other notaries. There were 40 violations in the implementation of notary duties and positions in the 2016-2020 period, during this period the increase and decrease in the level of violations of notary duties and positions in the Banten area was inconsistent. The implementation of sanctions imposed by MPW has not been optimal, as evidenced by the results of the study, namely an increase and decrease in the level of violations of notary duties and inconsistent positions in the region. In addition, there are several obstacles encountered by MPW as a body that supervises notaries, namely the lack of cooperation between notaries and MPW in enforcing the UUJN and the Notary Code of Ethics, the indifferent attitude shown by the notary during the examination session and the busyness of each MPW member in their respective offices. each relevant agency. Some solutions that can be done are routinely conducting socialization in terms of increasing notary professionalism, strengthening relations between notaries and MPW as well as conducting internal, external, repressive and preventive supervision.